P PENGARUH EXPRESSIVE WRITING DAN TERAPI DZIKIR TERHADAP SMARTPHONE ADDICTION DENGAN KEJADIAN NOMOPHOBIA - dewy, Tika Sari (Journal of Nursing Invention, 2023)
Background: Nomophobia is anxiety when away from a smartphone. Therapy that can be used to reduce nomophobia is writing therapy and dhikr therapy. One of the writing therapy used is expressive writing. Objective: The aim of this study was to determine the effect of the combination of expressive writing and dhikr therapy on smartphone addiction with nomophobia in students aged 10-14 years. Method:This Researchwas quasi-experimental with one group without a control group pretest-posttest design. The sample was 33 respondents with a purposive sampling technique. Result:This study showed that the difference before and after the intervention resulted in a moderate level of nomophobia, where the statistical test results used the paired t test with a p value of 0.002 (<0.05). Conclusion: Parents mustcontrol the use of smartphones, and transfer interest in expressive writing to adolescents so as to minimize the occurrence of nomophobia